2011
DOI: 10.1097/phm.0b013e3182389fae
|View full text |Cite
|
Sign up to set email alerts
|

Improving Balance Skills in Patients Who Had Stroke Through Virtual Reality Treadmill Training

Abstract: Neither traditional treadmill nor VR treadmill training had any effect on balance skill during quiet stance, but VR treadmill training improved balance skill in the medial-lateral direction better than traditional training did. VR treadmill training also improved balance skill during sit-to-stand transfers and the involvement of paretic limb in level walking more than the traditional one did.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
93
0
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(107 citation statements)
references
References 16 publications
5
93
0
9
Order By: Relevance
“…The difference may be due to the dissimilar evaluation and training procedures used. Furthermore, Yang et al (2011) found no significant improvement in center of pressure-related measures and symmetric indices after virtual reality treadmill training for 3 weeks (3 sessions, 20 min per week), but found a significant improvement in the paretic leg stance phase and paretic foot contact area during walking.…”
Section: Disscussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The difference may be due to the dissimilar evaluation and training procedures used. Furthermore, Yang et al (2011) found no significant improvement in center of pressure-related measures and symmetric indices after virtual reality treadmill training for 3 weeks (3 sessions, 20 min per week), but found a significant improvement in the paretic leg stance phase and paretic foot contact area during walking.…”
Section: Disscussionmentioning
confidence: 94%
“…The virtual reality balance training used in this study and in a previous treadmill training study (Yang et al 2011) involve a weight-shift in various directions. Postural control skills learned during dynamic challenges may be inappropriate for maintaining static postural stability (Yang et al 2011).…”
Section: Disscussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treadmill training is a task-oriented and repetitive activity 21) that improves strength 5) and symmetry 22) in the lower extremities as the slope progressively increases. It also reorganizes motor regions of the central nervous system and activates the cerebral cortex to cause motor learning in the limbs and eventually improves motor learning and balance 23) .…”
Section: Discussionmentioning
confidence: 99%
“…Stroke patients who have experienced repeated falls continue to fear that it will happen again, and their activity level decreases by about 25% 4) . This decreased activity makes daily independent activities difficult and results in decreased quality of life 5) . Moreover, self-efficacy is considered as important as physical ability influencing human movement and improvement of falls self-efficacy in stroke patients is associated with enhancement of balance and motor function 6) .…”
Section: Introductionmentioning
confidence: 99%